Topical administration of 40% soursop (Annona muricata) leaves extract cream prevented melanin elevation in UVB-rays exposed guinea pigs (Cavia porcellus) skin - Maya Cesarya Simangunsong; Wimpie Pangkahila; Anak Agung Gede Putra Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: Chronic exposure to UV light can cause skin abnormalities such as hyperpigmentation due to increased amount of melanin. Soursop (Annona muricata) leaf is a plant that contain flavonoids, polyphenols and antioxidants so that they have the potential as anti- hyperpigmentation. The purpose of this study was to prove that topical administration of 40% soursop leaf extract cream prevents melanin elevation in UVB-rays exposed guinea pigs skin. Methods: This study was an experimental study using randomized posttest only control group design. Subjects were 36 male guinea pigs (Cavia porcellus), brown, adult (3 months old), weighing 300-350 grams which were divided into two groups (n= 18). One group as the negative control group that was exposed to UVB and treated with basic cream (P0), and another group as the treatment group that was exposed to UVB and treated with 40% soursop (Annona muricata) leaves extract cream. The amount of melanin was measured histopathologically using immunohistochemical Masson-Fontana staining. Results: The results showed that the average amount of melanin in control group was 13.756 ± 5.2120, whereas in the 40% soursop (Annona muricata) treatment group was 6.811 ± 2.8105. Comparative analysis using independent t-test showed the p value of <0.001, thus indicating a significant difference between groups after treatment. Conclusion: Based on the results of this study it can be concluded that topical administration of 40% soursop (Annona muricata) leaves extract cream prevented melanin elevation in UVB- rays exposed guinea pigs (Cavia porcellus) skin.